2001
DOI: 10.1007/s004350000030
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure and formation of the body cavity lining in Phoronis muelleri (Phoronida, Lophophorata)

Abstract: Among other characteristics a trimeric coelomic compartmentation consisting of an anterior protocoel, followed by a mesocoel and a posterior metacoel is traditionally believed to substantiate the sister-group relationship between Lophophorata and Deuterostomia, together forming the Radialia. As molecular data cannot support this hypothesis a reanalysis of the coelomic cavities in Phoronida is undertaken, because corresponding coelomic compartmentation is widely accepted to support the Radialia hypothesis. A co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 29 publications
2
53
0
5
Order By: Relevance
“…However, in the last decade, the morphological evidence for a close relationship between the lophophorate groups and the deuterostomes has become weaker by careful re-examinations of the characters. It has been shown that neither brachiopods nor phoronids possess three coelomic cavities, because a protocoel is lacking in all lophophorate groups (Lü ter 2000; Bartolomaeus 2001). Thus, the archicoelomate concept (Siewing 1980) uniting Lophophorata and Deuterostomia, founded on the similarities of three distinct coelomic cavities, lost its basis.…”
Section: Results and Discussion (A) Deuterostome Versus Lophotrochozomentioning
confidence: 99%
“…However, in the last decade, the morphological evidence for a close relationship between the lophophorate groups and the deuterostomes has become weaker by careful re-examinations of the characters. It has been shown that neither brachiopods nor phoronids possess three coelomic cavities, because a protocoel is lacking in all lophophorate groups (Lü ter 2000; Bartolomaeus 2001). Thus, the archicoelomate concept (Siewing 1980) uniting Lophophorata and Deuterostomia, founded on the similarities of three distinct coelomic cavities, lost its basis.…”
Section: Results and Discussion (A) Deuterostome Versus Lophotrochozomentioning
confidence: 99%
“…However, no coelom but only ECM and isolated muscle cells are found in these structures (Lü ter, 1996(Lü ter, , 2000. In Phoronis muelleri as well as in Phoronis ovalis, the epistome does not contain a coelomic cavity, but only ECM and muscle processes (Bartolomaeus, 2001;Gruhl et al, 2005).…”
Section: Epistome Cavitymentioning
confidence: 99%
“…In contrast to such far-reaching hypotheses, the organ itself remained relatively poorly studied. In Phoronida as well as Brachiopoda, ultrastructural studies have found no support for a separate coelomic cavity in the epistome in representatives of these taxa (Lü ter, 1996;Bartolomaeus, 2001;Gruhl et al, 2005), although this had been suggested by earlier investigations (e.g., Siewing, 1973;Emig and Siewing, 1975;Herrmann, 1980;Zimmer, 1980). In phylactolaemate bryozoans, there is clearly no evidence for a tripartion of the coelom at any time during embryonic development (Mukai, 1982;Nielsen, 2001).…”
mentioning
confidence: 92%
“…Each of these body regions was originally described as having a true coelomic cavity lined by mesoderm and were interpreted as the protocoel (epistome), mesocoel (lophophore), and metacoel (trunk), linking this arrangement to the tripartite coeloms found in echinoderms (Masterman 1898 ). The epithelial lining of the epistome in two species of Phoronis was found instead to be myoepithelial cells lacking adherent junctions surrounding a gel-like extracellular matrix, thus not exhibiting the features of a true epithelial layer (Bartolomaeus 2001 ;Gruhl et al 2005 ). Further complicating these fi ndings are ultrastructural observations of the epistome lining of Phoronopsis harmeri , which does contain adherent junctions (Temereva and Malakhov 2011 ).…”
Section: Introductionmentioning
confidence: 81%
“…These cells will form a small cavity underneath the apical tuft region of the late gastrula. This cavity has been interpreted as the fi rst coelomic cavity ("protocoel"), but as discussed previously, whether these cells form a true epithelium in all or in just select species is debated (Zimmer 1978 ;Bartolomaeus 2001 ;Temereva and Malakhov 2006 ). At this asymmetric late gastrula stage, the gut is a blind sac.…”
Section: Early Developmentmentioning
confidence: 97%